SEMICOLON BATIK MOTIVES AND ITS APPLICATION TO CASUAL CLOTHES - Pramesti, Julieta Citra; -, Guntur (Runtas: Jurnal Fesyen dan Wastra Nusantara, 2023)
A semicolon is a semicolon (;). This semicolon punctuation in writing serves as a substitute for a conjunction in a sentence. In a sentence the use of a semicolon is not intended as the end of a sentence for the author. In the lives of people with mental disorders , the use of this punctuation mark is a statement of self to survive, to avoid fatalistic actions (suicide). Semicolon mental disorder as the theme of the work is motivated by the socialization constraints of the sufferer's community and their self-expression. Semicolon is a sign used by individuals or communities to show themselves and the suffering they experience. As a sign, the semicolon is interesting to be used as inspiration in the creation of batik motif designs. Its application in casual clothing is to provide another alternative in expressing self-identity. Through exploration, design, and embodiment, the Seroja Sauntara motif is created ; Roman Wani; Lang Aruna; and Semisulur . As for its application to clothing, namely Eunoia, Tittari, Renjana, Upeksha, and Sattva . The title of the work is adapted to the character and appearance, as a means of self-healing .